2019
DOI: 10.3390/w11030440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stoniness on the Hydraulic Properties of a Soil from an Evaporation Experiment Using the Wind and Inverse Estimation Methods

Abstract: Stony soils are distributed all over the world. The study of their characteristics has gained importance lately due to their increasing use as agricultural soils. The effect that rock fragments exert on the soil hydraulic properties is difficult to measure in situ, and is usually derived from the fine earth properties. However, the corrections used so far do not seem accurate for all types of stony soils. Our objective was to assess the adequacy of estimating the hydraulic properties of a stony soil from the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…HYPROP uses the simplified evaporation method (Schindler, 1980), improved by Peters & Durner (2008b) and Peters et al (2015) to determine the SHPs. The method has been applied successfully for measuring the SHPs of stony soils (Arias et al, 2019;Beckers et al, 2016;Naseri et al, 2019). The samples were allowed to evaporate from the top in a laboratory, in which air humidity and temperature are controlled to ensure an almost constant potential evaporation rate.…”
Section: The Evaporation Methods For Measuring the Shpsmentioning
confidence: 99%
See 2 more Smart Citations
“…HYPROP uses the simplified evaporation method (Schindler, 1980), improved by Peters & Durner (2008b) and Peters et al (2015) to determine the SHPs. The method has been applied successfully for measuring the SHPs of stony soils (Arias et al, 2019;Beckers et al, 2016;Naseri et al, 2019). The samples were allowed to evaporate from the top in a laboratory, in which air humidity and temperature are controlled to ensure an almost constant potential evaporation rate.…”
Section: The Evaporation Methods For Measuring the Shpsmentioning
confidence: 99%
“…of stony soils were reviewed by Bagarello and Iovino (2007) and later by Beckers et al (2016) and Naseri et al (2019Naseri et al ( , 2020. Arias et al (2019) used the wind evaporation method to measure SHPs of a silt loam stony soil with 40% volumetric RF and applied inverse modeling to identify the effective SHPs. They reported that using only the volume of RF to scale the WRC of the stony soil is inappropriate.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of the evaluated models for scaling K s , the Maxwell model yields the closest match to the numerically identified values of K r . We note that these results may differ in natural soils, where an increase in the saturated hydraulic conductivity might be expected because of macropore flow in lacunar pores at the interface between the background soil and RFs (Beckers et al, 2016;Hlaváčiková et al, 2016;Arias et al, 2019). We have not included such a process in our 3D simulations.…”
Section: Comparison Of the Relative K S Of The Scaling Models And The...mentioning
confidence: 99%
“…We note that these results may differ in natural soils, where an increase of the saturated hydraulic conductivity might be expected because of macropore flow in lacunar pores at the interface between background soil and rock fragments (Beckers et al, 2016;Hlaváčiková et al, 2019, Arias et al, 2019. We have not included such a process in our 3D simulations.…”
Section: Maxwell Model Reduces Tomentioning
confidence: 99%